The environmental context of a city in decline: The vegetation history of a Khmer peripheral settlement during the Angkor period. (April 2019) - Hall, Tegan; Penny, Dan; Hamilton, Rebecca
Abstract: During the Angkor period (9th to 15th centuries C.E.) the Khmer kingdom extended across much of mainland Southeast Asia. The primate city of Angkor was located on the floodplains to the north of the Tonle Sap and connected to a network of secondary cities across the kingdom via formal road or navigable river systems. Preah Khan of Kompong Svay was one such secondary city, and was positioned on the eastern margins of Khmer territory approximately 100 km from Angkor. Stylistic dating of Preah Khan's temple architecture revealed that the majority of building works was conducted between the 11th and 13th centuries C.E., however only minimal archaeological evidence for occupation during this period has been found. This paper presents a record of environmental change that re-evaluates the settlement history of Preah Khan, and suggests that occupation and land use change was occurring at least between the early 12th and late 14th centuries C.E. Signs of gradual land use attenuation and a reduction in water infrastructure management are evident from the late 13th century through to the late 14th century C.E., and during the mid-14th century an apparent shift in the utilisation of the city occurs. This study helps to address the relative lack of research into cities outside the Angkor region, and demonstrates the value of using palaeoecological evidence for unravelling the complexity of settlement history in Angkor-period cities, particularly through the waning phases of occupation. Highlights: Preah Khan of Kompong Svay was a secondary city with a complex occupation history Land use attenuation began sometime between the late 13th and late 14th century C.E. A shift in the function and use of the city occurred during the mid-14th century C.E. Palaeoecological data is of great utility in reconstructing settlement narratives